Influencia de los centros de enseñanza automovilísticos en el conocimiento de los conductores en las vías en cuanto a normatización (2013)
Currently citizens who are interested in obtaining a driver's license must meet certain requirements required by the Ministry of Transportation and the District Education Secretary. These governmental entities are in charge of verifying the fulfillment of these conditions in the Automobile Education Centers, in order to take care of the life of the future drivers and protect the safety of the pedestrians and other drivers in the roads of Bogotá D.C. Road accidents caused by vehicle drivers, both public and private, are one of the leading causes of violent death, both nationally and globally, according to the World Health Organization. The figures of people injured and killed as a result of these accidents are alarming because according to the statistical database of the accident statistics yearbook issued by the Ministry of Transport, it indicates that the percentage figures for road accidents tend to increase per year. The director of the Driver Recognition Centers (CRC) Germán Vargas informed that approximately 30% of the driving licenses of Colombians are false, which indicates that the owners of these licenses are people who did not perform the required procedures, therefore they do not know the theory corresponding to the traffic regulations and the adequate use and behavior on the roads. In order to understand the demands that are required of an Automobile Education Center it is necessary to know the legal, institutional and social parameters that these must have. It is necessary to take into account that all the Automotive Education Centers are a non-formal and commercial teaching establishment. Therefore, they must comply with certain norms, laws, decrees and requirements for their free functioning, said the above is of great importance that these institutions offer the complete classes to their students following the instructions demanded by the governmental entities in charge in order to guarantee society responsible drivers and aware of their actions at the time of driving. In order to determine the knowledge of drivers with a valid driver's license, a study will be conducted to diagnose the level of knowledge regarding traffic regulations and behavior on the roads, in order to propose a management system for the centers of Automotive education where awareness and understanding of traffic regulations are increased, in order to decrease the irresponsibility and road accident rates.